Implementasi Edupreneurship Bagi Siswa SMK Perikanan dan Kelautan Puger (Kabupaten Jember) - Reviana (Reviana/Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to describe the implementation of edupreneurship in shaping students' readiness to face the world of entrepreneurship and the challenges of the working world at Puger Jember Fisheries and Maritime Vocational Higt School. Edupreneurship in this school is implemented through three main programs, namely 1) Teaching Factory (TEFA), 2) Industrial Work Practice (IWP), and 3) Service Production Unit (SPU), which involves students directly in production activities, business management, and interaction with the industrial world. This uses a descriptive research with a qualitative approach, the research subjects deputy principal for curriculum, productive teachers, and students. Data were collected throught interviews, observations, and documentation and analyzed using the stages of data reduction, data display, and conclusion drawing/verification. Meanwhile, to test the validity of the data is used triangulation of sources. The results of the study indicate that the implementation of edupreneurship has an important role in improving student readiness. Through TEFA students gain real experience related to production processes, cost management, and product quality. While IWP provides direct experience regarding industrial work culture, discipline, and adaptability. Meanwhile, SPU trains students in managing simple businesses, including calculating capital, profits, and marketing strategies. In conclusion, these three programs enhance both technical and non-technical skills, thereby shaping work attitudes and fostering an entrepreneurial spirit in students, as well as strengthening their ability to face challenges in the workplace and the entrepreneurial world. Keywords: Edupreneurship, Teaching Factory, Industrial Work Practice, Service Production Unit
Approved by Teddy